Pneumococcal Polysaccharide Vaccine Ameliorates Murine Lupus - Cantarelli, Chiara; Guglielmo, Chiara; Hartzell, Susan; Salem, Fadi El; Andrighetto, Sofia; Gazivoda, Victor P.; Fiaccadori, Enrico; La Manna, Gaetano; Zaza, Gianluigi; Leventhal, Jeremy; Tassiulas, Ioannis; Cravedi, Paolo (Frontiers in Immunology, 2019)
Current guidelines encourage administering pneumococcal vaccine Prevnar-13 to patients with lupus, but whether such vaccinations affect disease severity is unclear. To address this issue, we treated 3-month-old MRL-lpr mice, that spontaneously develop a lupus-like syndrome, with Prevnar-13 or vehicle control. After 3 months, we quantified circulating anti-Pneumococcal polysaccharide capsule (PPS) antibodies and signs of disease severity, including albuminuria, renal histology, and skin severity score. We also compared immunophenotypes and function of T and B cells from treated and untreated animals. Prevnar-13 elicited the formation of anti-pneumococcal IgM and IgG. Prevnar-13 treated animals showed reduced albuminuria, renal histological lesions, and milder dermatitis compared to vehicle-treated controls. Mitigated disease severity was associated with reduced and increased T follicular helper cells (TFH) and T follicular regulatory cells (TFR), respectively, in Prevnar-treated animals. T cells from Prevnar-13 vaccinated mice showed differential cytokine production after aCD3/aCD28 stimulation, with significantly decreased IL-17 and IL-4, and increased IL-10 production compared to non-vaccinated mice. In conclusion, pneumococcal vaccination elicits anti-pneumococcal antibody response and ameliorates disease severity in MRL-lpr mice, which associates with fewer TFH and increased TFR. Together, the data support the use of Prevnar vaccination in individuals with SLE.